KEBIJAKAN PEMERINTAH DALAM MENANGGULANGI POLUSI DI DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KABUPATEN KARAWANG - Dwi Juliawati; Kariena Febriantin; Dadan Kurniansyah (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Air pollution is an environmental problem that often occurs in areas with high productivity. There are many companies that stand on people's land in the Karawang area, with the number of industrial companies increasing every year. Vehicle transportation activities and industrial factory waste disposal activities are a source of air pollution in Karawang Regency. This study aims to determine the policies made by the government of Karawang Regency, especially the Department of Environment and Hygiene in tackling pollution in Karawang. The method used in this research is a qualitative approach method. The results showed that in dealing with air pollution, Karawang Regency issued environmental permits and carried out monitoring of environmental impacts (AMDAL). The role of DLHK Karawang Regency is not only to formulate a policy, but to actively participate in implementing policies with the community.